Pengaruh Intensitas Penggunaan Generative AI terhadap Niat Berwirausaha Digital: Studi pada Digital Product Manager di Indonesia - Raka Pradana Kostarian; Eddy Soeryanto Soegoto; Shinta Wanda Kusuma Modjo (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The Indonesian technological landscape is undergoing a fundamental shift, characterized by a 92% AI adoption rate in the workplace. As Digital Product Managers evolve into strategic AI-powered orchestrators, there is a growing need to understand how this technology influences career transitions. This research aims to analyze the influence of Generative AI usage intensity on digital entrepreneurial intention among Digital Product Managers in Indonesia. Adopting a quantitative descriptive-correlational design, the study surveyed 50 professionals selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM). The findings demonstrate that Generative AI usage intensity exerts a strong, positive, and significant influence on digital entrepreneurial intention. The model explains 77.2% of the variance in the dependent variable. AI integration provides significant weekly time savings, which professionals reallocate as cognitive assets for business experimentation and strategic planning. By lowering technical barriers and democratizing prototyping, Generative AI acts as a psychological catalyst that enhances self-efficacy and mitigates perceived risks. These results provide strategic insights for policymakers and talent developers to bolster the national digital entrepreneurship ecosystem.